Dissolution behaviour and imageability of ternary borate glasses for use in geniculate artery embolization - R. A. Manchester; T. Z. Todorova; E. Tonkopi; B. Kelly; J. Gosse; C. Davis; K. Brewer; M. Shymka; D. Boyd (Discover Materials, 2021)
Abstract Sixteen borate glass compositions comprising K2O and SrO were screened, using a design of mixtures approach, to model compositional effects on dissolution, CT imageability, and MRI relaxivity (R2). Based on the characteristics of each network, together with dose determination and toxicological risk, the composition identified as BKSA16 was selected as a preferred composition for pre-clinical evaluations related to geniculate artery embolization (GAE). Accordingly, BKSA16 particles were subjected to a flame spheroidization process and recharacterized, including the evaluation of residual mass at 72 h in physiologically representative media along with clinical determinations of suspension time (ease of use). For both the irregular particles and microspheres residual mass was present at 72 h in physiologically representative media. Additionally, both the microspheres and irregular particles achieved suspension times deemed to be acceptable for clinical use. The collective data confirms that BKSA16 microspheres have a range of beneficial features (specifically both degradable and imageable) suited to GAE.